A QUANTUM CHEMICAL STUDY OF THE CONFORMATION OF ALINIDINE A NEW ANTIARRHYTHMIC AGENT (Journal of Sciences, Islamic Republic of Iran)
The conformation of alinidine a new and specific bradycardic agent was studied using MNDO method. It has been found that the rotation of both phenyl and imidazoline ring of this compound is restricted. Of two possible isomers of irnidazoline ring, the one with NH in the cis position to allyl side chain is slightly more stable. On the other hand, the allyl group can rotate freely and at least six more conformers besides that of global minima has been identified. These calculations show that alinidine has a rather flexible structure and suggest that synthesis of more rigid analogs of this compound may be interesting from the structure-activity point of view